KETERAMPILAN PROSES SAINS PADA MATERI BAYANGAN CERMIN MELALUI E-LKM BERBASIS INKUIRI TERBIMBING - Nur Chalimatus Sholihah; Tutut Nurita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the improvement of students' science process skills through the implementation of guided inquiry-based E-LKM on the material of mirror image formation. The research method used is pre-experimental with a one group pretest-posttest design. The subjects were 32 students of class VIII A MTSN 4 Surabaya City. The instruments used included a science process skills test, an observation sheet of learning implementation, and a student response questionnaire. Data were analyzed using N-Gain, the Shapiro-Wilk normality test, and a paired sample t-test. The results showed that the average pretest score of 41.33 increased to 80.31 in the posttest with an N-Gain value of 0.66 in the moderate category. The results of the statistical test showed a p value , which means there was a significant increase. Improvements also occurred in all indicators of science process skills, with high categories in the indicators of formulating problems and identifying variables. The implementation of learning was in the very good category and student responses showed positive results. Thus, guided inquiry-based E-LKM is effective in improving students' science process skills on the material of mirror image formation.